2008
DOI: 10.1089/thy.2008.0257
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism Has an Adverse Effect on Human Spermatogenesis: A Prospective, Controlled Study

Abstract: Hypothyroidism has an adverse effect on human spermatogenesis. Morphology is the only sperm parameter that is significantly affected. Motility may also be affected, but further studies regarding this are needed. Screening for thyroid dysfunction in males who present with a defect in spermatogenesis is strongly recommended, and if hypothyroidism is noted, the response to thyroid hormone should be evaluated before initiating other treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 33 publications
(24 reference statements)
4
53
0
10
Order By: Relevance
“…Thyroid hormone receptors have been reported in the testis (17); T 3 stimulates Sertoli cell function and mRNA expression of inhibin B and regulates Leydig cell function as well. In humans, hypothyroidism has effects on spermatogenesis with morphological changes and alteration in sperm motility (18). In rats, hypothyroidism results in arrested proliferation of germ cells (19) and in hypothyroid rams in reduced sperm motility (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid hormone receptors have been reported in the testis (17); T 3 stimulates Sertoli cell function and mRNA expression of inhibin B and regulates Leydig cell function as well. In humans, hypothyroidism has effects on spermatogenesis with morphological changes and alteration in sperm motility (18). In rats, hypothyroidism results in arrested proliferation of germ cells (19) and in hypothyroid rams in reduced sperm motility (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, in hypothyroid males, testosterone and free testosterone are low and estradiol levels are normal (18,24) and have no apparent impact on gonadotrophin secretion because there is no reciprocal increase in FSH and LH. In sheep and rats, inhibin B suppresses FSH synthesis and secretion (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, proponents of this hypothesis primarily cite in utero and infancy as the key exposure periods for effects to occur (9,22,140). Hypothyroidism can adversely affect spermatogenesis (141), but because only morphology is affected and, as noted previously, there is essentially no evidence that soy adversely affects thyroid function in healthy individuals, no further comment about this relationship will be made (116).…”
Section: Sperm and Semen Effectsmentioning
confidence: 99%
“…Nevertheless, TRs were also identified in spermatogenic germ cells undergoing differentiation, suggesting a possible role for thyroid hormone in normal spermatogenesis and metabolism in the adult testis. Although studies that have specifically focused on thyroid hormone effects in spermatogenesis are by far limited, some recent reports have demonstrated that altered thyroid status in adult males is associated with abnormal spermatogenesis in animals and humans (Faraone-Mennella et al, 2008;Krassas and Pontikides, 2004;Krassas et al, 2008a;Meeker et al, 2007;Weng et al, 2007). Although, collectively, these results suggest that thyroid hormone might play a role in the endocrine regulation of spermatogenesis, the potential biological importance of TRs in germ cells remains to be established.…”
Section: The Ontogeny Of Thyroid Hormone Nuclear Receptors In Testismentioning
confidence: 99%